Intravenous Thrombolysis Outcomes in Patients Presenting with Large Vessel Acute Ischemic Strokes—CT Angiography‐Based Prognosis. Issue 2 (3rd June 2014) - Rai, Ansaar; Cline, Brendan; Williams, Eric; Carpenter, Jeffrey; Roberts, Thomas
ABSTRACT: BACKGROUND AND PURPOSE: To establish outcome rates for patients receiving intravenous thrombolysis based on vascular occlusion site. METHODS: This is a retrospective analysis of 225 patients who had received intravenous‐rt‐PA for anterior circulation strokes. The occlusion‐site was prospectively determined on the admission computed tomographic angiography (CTA) and divided into: large vessel occlusion (LVO) including patients with an internal carotid artery terminus or middle cerebral artery (M1/proximal M2) occlusions and no large vessel occlusion (No‐LVO; distal M2/M3/ACA) including patients with either distal or no occlusions. The primary outcome was the modified Rankin score (mRS) at 90‐days with a good outcome defined by mRS of 0‐2.000. RESULTS: There were 114 (50.7%) patients in the LVO and 111 (49.3%) in the No‐LVO group. A good outcome was seen in 28 (24.6%) patients in the LVO and 77 (69.4%) patients in the No‐LVO group (OR .14; 95% CI: .08‐.26; P < .0001). Mortality was observed in 13 (11.7%) patients in the No‐LVO group and 48 (42.1%) patients in the LVO group (OR .18; 95% CI: .09‐.36; P < .0001). Significant hemorrhage was seen in 14 (12.5%) patients in the LVO and 0 (0%) patients in the No‐LVO group ( P < .0001). Older age (OR .96; 95% CI: .93‐.98; P = .002) and presence of LVO (OR .29; 95% CI: .12‐.68; P = .004) were significant independent predictors of poor outcome. CONCLUSION: CTA identification of proximal occlusions is associated with significantly poor outcomes in patients receiving intravenous stroke thrombolysis.